Physical Functional Capacity and C-Reactive Protein in Schizophrenia - Szortyka, Michele Fonseca Vieira; Cristiano, Viviane Batista; Ceresér, Keila Maria; Francesconi, Lenise Petter; Lobato, Maria Inês; Gama, Clarissa; Belmonte-de-Abreu, Paulo (Frontiers in Psychiatry, 2016)
Introduction: Schizophrenia is a severe, debilitating mental disorder that affects both the physical health and the functional capacity of patients, causing great impairment throughout the life course. Although physical and cognitive impairments may represent different expressions of a single systemic inflammatory process, little is known about the relationship between motor function and schizophrenia. Objective: To evaluate physical functional capacity in patients with schizophrenia and ascertain whether it correlates with markers of inflammation, disease severity, and pharmacotherapy. Methods: Cross-sectional study using a convenience sampling strategy. Forty patients with stable schizophrenia, undergoing treatment, were recruited from the Outpatient Program of Hospital de Clínicas de Porto Alegre, University Hospital linked to Public Health System. Physical functional capacity was assessed by the 6-minute walk test (6MWT), and inflammatory markers were measured by C - reactive protein (CRP) and Von Willebrand Factor (VWF). Results: Mean functional capacity and clinical variables differed among patients and Brazilian population regarding heart rate (p=0.004), diastolic (p=0.001) and systolic (p<0.001) blood pressure, respiratory rate (p<0.001), CRP (p=0.015), Borg Scale of Perceived Exertion scores (p<0.001), and 6MWT both in men (p<0.001) and women (p=0.024). Additionally, 6MWT and dyspnea in Borg Scale of Perceived Exertion scores (BSPE) were positively associated to CRP (r=-.369, p=.019) and r=-.376, p=.017) and r=0.354, p=0.025 and r=0.535, p<0.001, respectively). Conclusion: The present study detected significant association between measures of functional impairment and markers of inflammation, especially elevated CRP in a group of stable outpatients with DSM-IV and ICD10 diagnosis of schizophrenia. Possible explanations for the associations could be linked to continued use of antipsychotics, although underlying neuroinflammatory mechanisms directly related to illness (schizophrenia) could not be ruled out. The findings of this study expand evidences of neuroinflammation to systemic inflammation in schizophrenia linking it to alterations of physical functional capacity and point to the need of additional studies exploring general inflammation and novel therapeutic interventions.